The relationship between types of innovation and SMEs’ performance: A multi‑dimensional empirical assessment. - Expósito-García, Alfonso; Sanchis-Llopis, Juan Alberto (Springer Nature, 2019)
This paper examines the impact of different types of innovation on the business performance of small and medium-sized enterprises (SMEs) using a multi-dimensional analytical approach. Based on a wide sample of Spanish SMEs, our results highlight the existence of positive impacts of innovation on financial and operational dimensions of business performance, and the significant differences in these impacts depending on the type of innovation and the performance indicator considered. Our findings are relevant for managers and innovation decision-makers when designing innovation strategies to foster the business performance of SMEs. Additionally, the multi-faceted nature of the link between innovation and business outcomes in SMEs reveals that making the right innovation decision is crucial in securing the desired performance outcomes in a context of limited resources for innovation.
https://openpolicyfinder.jisc.ac.uk/id/publication/36024
Keywords: Empresas - Gestión; Pequeñas y medianas empresas; Creatividad en la empresa; Innovation; Business Performance; multi-dimensional analysis; SME